The impact of selected subsidy program on household poverty in rural area in Sabah - Lina Encharang; Kassim Mansur; Mori Kogid (Asian Scholars Network, 2022)
This study examined the impact of three different categories of subsidy on poverty in eight rural districts in Sabah in 2009until 2016. The three categories of subsidy are selected consumer items (sugar, wheat flour, cooking oil-1kg in polybag, and rice), petrol and diesel, and liquefied petroleum gas (LPG) subsidy. Poverty is dependent variable, meanwhile selected consumer items, petrol and diesel, and liquefied petroleum gas (LPG) subsidies are used as independent variables. Random effect is chosen to examine the stationary of the data. From the test it was found that dependent variable has positive relationship with independent variables, which the increasing of subsidies will increase of number of poverty in household. There are many other factors that contribute to the positive relationship between poverty and subsidy. The delivery system of subsidy in rural areas is the main issue in this subsidy program. Leakages and middleman are main issue in the delivery system. Thus, as a recommendation a new approach is needed to make sure this subsidy program is more effective and reach the target group